Applications of the Zingiberaceae in traditional medicine among the Dayak Tamambaloh Tribe in Labian Ira'ang and Temau Villages, Kapuas Hulu District, Indonesia - MARKUS IYUS SUPIANDI; HENDRIKUS JULUNG; YUDITA SUSANTI; DIDIN SYAFRUDDIN; ADRIANA GANDASARI; SUSRIYATI MAHANAL; SITI ZUBAIDAH (Society for Indonesian Biodiversity, 2024)
Abstract. Supiandi MI, Julung H, Susanti Y, Syafruddin D, Gandasari A, Mahanal S, Zubaidah S. 2024. Applications of the Zingiberaceae in traditional medicine among the Dayak Tamambaloh Tribe in Labian Ira'ang and Temau Villages, Kapuas Hulu District, Indonesia. Biodiversitas 25: 71-78. This indigenous knowledge remains largely undocumented, primarily in oral form and only possessed by specific individuals. Therefore, this study aimed to record the Zingiberaceae species systematically applied for traditional medicine by the Dayak Tamambaloh Tribe, Kapuas Hulu District, Indonesia through a qualitative descriptive method. Data were collected from informants and recommendation sources through different stages including a literature study, semi-structured interviews, field observations, and documentation, for subsequent analysis using descriptive methods. The results showed that Labian Ira'ang Village inhabitants utilize eight Zingiberaceae species, namely lengkuas (Alpinia galanga), lalamas (A. nieuwenhuizii), kunus baute (Curcuma zedoaria), kunus kuning (C. longa), tantamu kuning (C. xanthorhiza), sakur (Kaempferia galanga), japa (Zingiber montanum), and laia (Z. officinale). Meanwhile, the tribe in Temau reported nine species, including lqngkuas (A. galanga), kunus baute (C. zedoaria), kunus (C. longa), tantamu kuning (C. xanthorhiza), katimbang (Etlingera coccinea), randar (Hornstedtia havilandii), sakur (K. galanga), japa (Z. montanum), and laiya (Z. officinale). The results show the same types of plants used by people in Labian Ira'ang and Temau Villages, although the processing methods and uses differ. The difference is due to different experiences in gaining knowledge about using plants as traditional medicine.